(untitled) (Mustansiria Dental Journal, 2018)
The present study evaluated the effect of recasting cobalt-chromium alloys with the addition of new alloy in different ratios (75% and 50%) on the deflection fatigue resistance using three types of alloys: Wironit (Bego), Remanium (Dentaurum), and Wisil (Wipla). Each alloy was divided into three groups for each test, group I (100% new alloy), group II (75% new alloy +25% recast alloy), and group III (50% new alloy + 50% recast alloy). Fatigue specimens produced were butterfly-shaped and half round at their cross section with 18mm length, 1mm thickness, and 2mm width. For each alloy group, five samples were prepared. The results of this study revealed that recasting with adding 75% new alloy did not significantly affect the fatigue resistance of Wironit and Wisil alloys, while significantly affected that of Remanium. Recasting with the addition of 50% new alloy significantly decreased the fatigue resistance of the three types of alloys. Wironit alloy showed the higher mean values for deflection fatigue resistance compared with Remanium and Wisil alloys.